Absence of lymphatics at the bone-implant interface: implications for periprosthetic osteolysis. - Edwards, J; Schulze, E; Sabokbar, A; Gordon-Andrews, H; Jackson, D; Athanasou, N (2008)
BACKGROUND: Wear particles, found at the bone-implant interface surrounding a loose prosthesis, are commonly phagocytosed by macrophages. Wear particles and wear particle-containing macrophages are also found in regional lymph nodes draining arthroplasty tissues. The means by which wear particles are transported from arthroplasty tissues to lymph nodes is uncertain, as the presence or absence of lymphatic vessels in periprosthetic tissues has not been established. METHODS: We determined immunophenotypic expression of LYVE-1 and podoplanin, two highly specific lymphatic endothelial cell markers, in the hip arthroplasty pseudocapsule surrounding the false joint and the bone-implant interface of the femoral and acetabular pseu-domembrane. RESULTS: LYVE-1+/podoplanin+ lymphatic vessels were not identified in the pseudomembrane but were found in the pseudocapsule. Normal bone did not contain lymphatic vessels. INTERPRETATION: Our findings suggest that the wear particles shed at the bone-implant interface are not transported to draining lymph nodes by lymphatics directly from the pseudomembrane, but via the pseudocapsule. The absence of a lymphatic clearance mechanism may contribute to accumulation of wear particles at the bone-implant interface and promote periprosthetic osteolysis through stimulation of osteoclast formation and activity.